2022
DOI: 10.1155/2022/7888076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics Therapy on Nonalcoholic Fatty Liver Disease

Abstract: Objective. Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease in the world. The pathogenesis of NAFLD is complex and multifactorial. Clinical studies have shown that alterations in the gut microbiota play a key role in NAFLD. The purpose of this study was to analyze the effect of probiotic supplementation on the treatment of NAFLD patients based on various indicators. Methods. We conducted a meta-analysis investigating the relationship between NAFLD and probiotic supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
0
9
1
1
Order By: Relevance
“…In our study, probiotic treatment had no significant effect on CRP and TNF-α. These are important indicators of the protective effect of probiotics on patients with MAFLD ( 48 – 50 ) The results of our study are not consistent with those of Pan ( 39 ), Khan ( 51 ), Gao ( 52 ), and Huang ( 53 ). In a meta-analysis, probiotic supplementation did not improve some measures of inflammation in patients with MAFLD ( 54 , 55 ).…”
Section: Discussioncontrasting
confidence: 91%
“…In our study, probiotic treatment had no significant effect on CRP and TNF-α. These are important indicators of the protective effect of probiotics on patients with MAFLD ( 48 – 50 ) The results of our study are not consistent with those of Pan ( 39 ), Khan ( 51 ), Gao ( 52 ), and Huang ( 53 ). In a meta-analysis, probiotic supplementation did not improve some measures of inflammation in patients with MAFLD ( 54 , 55 ).…”
Section: Discussioncontrasting
confidence: 91%
“…Although the molecular mechanism of probiotics is still not completely understood, it is clear that they can be used in the treatment of NAFLD as they modulate the gut microbiota. They also improve intestinal mucosal permeability and inhibit the inflammatory response [149].…”
Section: Probioticsmentioning
confidence: 99%
“…Although there are some drugs with hypolipidemic effects that can improve the symptoms of NAFLD, they may be accompanied by adverse side effects ( Romero-Gomez et al, 2017 ; Neuschwander-Tetri, 2020 ). Increasing numbers of studies have demonstrated that probiotics can effectively reduce endotoxemia, improve gut barrier function, and may play a certain role in the treatment of NAFLD ( Wang et al, 2020 ; Ferguson and Finck, 2021 ; Luo et al, 2021 ; Ren et al, 2021 ; Huang et al, 2022 ). As the most studied probiotic bacteria, Lactobacillus is an important member of the maintenance of microbial flora in the gut, and some strains have been widely used in the field of food and health and have been developed as probiotics ( Liang et al, 2020 ; Zhang et al, 2020 ; Lee et al, 2021 ; Yu et al, 2021 ; Zhu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%